Reviewed Study on Changing Values of Female Youth: Exploring the shifting values and roles of female youth in modern society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Youth comprise a significant area of the society. Being an age classification, they are youthful, dynamic and vivacious. They are cherished and enjoyed by the senior age. Youth population is a beam of trust in many debilitated and victims in the society. The previous mankind's history reports that they have been instrumental in bringing down the tyrant governments and ousting the years old despots. Youth have given help to such huge numbers of experiencing the treachery, monstrosities and enslavement. They are the future residents and can do a great deal for the development of society. Their investigation by utilizing logical methodology gives a great deal of data to numerous researchers. The chose issue investigates the changes occurring in the life of female youth that are a recognized piece of the youth population. They are practically half in numbers. Indian society hypothetically remembers them as the heavenly type of human race. The growing importance of female youth is the result of current modern society. Presently they are relied upon to play out a functioning job in the development of a production arranged society. In dominant part of the cases female youth are in the circumstance of predicament between tradition versus current ways of life.